Low Temperature Degradation and Mechanical Properties of Alumina Reinforced Ceria-Zirconia by Colloidal Processing. Issue 2 (February 2021) - Tovar-Vargas, D.; Ferrari, B.; Sanchez-Herencia, A.J.; Anglada, M.; Jimenez-Pique, E.
Highlights: Colloidal processing using modification of alumina particles surface charge to avoid agglomerates is a robust route to the obtention of dense alumina reinforced 10Ce-TZP ceramics. Grain size reduction for all the composites in comparison with pure 10Ce-TZP leading to enhanced mechanical properties. Low Temperature Degradation resistance increases with alumina additions between 0-15 wt%. Spherical indentations with different loads are presented to investigate the effects of alumina additions into the transformability of the material. Abstract: 10Ce-TZP base composites with 2.5, 5, 10 and 15 wt% alumina were fabricated by colloidal processing from slurries with 41 vol% solid load in order to investigate the effects of alumina in the final composites aging and mechanical properties. Alumina particle surface charge was modified with the addition of 3 wt% of PAA. The resulting composites have high relative densities (∼ 99%) and homogeneous alumina distribution. The microstructure is refined by the alumina addition resulting in a tetragonal-monoclinic microstructure with monoclinic phase content diminishing with alumina concentration down to 16 vol% in 10Ce-15Al2 O3 composite. From the study of hydrothermal aging in autoclave steam at 134 °C and 2 bar pressure, it is concluded that all composites have very high resistance to low temperature degradation. At the same time, mechanical properties were investigated by measuring hardness, elastic modulus, strength and t-m transformation around Vickers and spherical indentations. The t-m transformation extension around imprints prevents the formation of Vickers indentations cracks, which indicates a high level of damage tolerance for all compositions. In particular, for 10Ce-15Al2 O3 composite, an excellent combination of hardness (∼10 GPa), strength (∼1400 MPa), damage tolerance, and resistance to low temperature degradation is achieved.